Prevalence, risk factors and association with gallstone disease of non-alcoholic fatty liver disease among rural indigenous communities : A cross-sectional study in Sarawak, Malaysia - Yew, Ting Ting; Cheah, Whye Lian; Koa, Ai Jiun; Chow, Han Bing (Academy of Family Physicians of Malaysia (AFPM), 2025)
Introduction: This study aimed to evaluate the prevalence and risk factors of non-alcoholic fatty liver disease (NAFLD) among Dayak communities in Malaysia, shedding light on an underexplored population. Methods: A cross-sectional study was undertaken among Dayak villagers in Sarawak aged 18 years and above using an interview-based questionnaire, followed by an anthropometric measurement, a blood test and an abdominal ultrasound. Results: A total of 324 participants met the inclusion criteria. Among them, 42.9% were men, and the mean age was 49.85±14.9 years. The prevalence of NAFLD was substantially high at 58%, with 43.1% of the participants having mild fatty liver (grade 1). NAFLD was closely associated with waist circumference and body mass index (BMI) (P<0.001). Central obesity, as indicated by waist circumference and BMI, emerged as a potent risk factor, with higher values correlating with an increased likelihood of NAFLD. A higher prevalence of NAFLD was observed in the participants with an advancing age, an elevated triglyceride level (66.7%) and a lower high-density lipoprotein cholesterol level (81.6%). However, these associations did not remain significant in the multivariate analysis. Gallstones, which share common risk factors with NAFLD, were not significantly associated with NAFLD in this population (P=0.853). Conclusion: This study defines the prevalence and association of NAFLD with sociodemographic characteristics, health profiles and gallstone disease among indigenous villages in Dayak communities. A high BMI and central obesity are found to be independent risk factors of NAFLD.